Imperial Emotions : Cultural Responses to Myths of Empire in Fin-de-Siècle Spain - Krauel, Javier, 1972- (Book collections on Project MUSE., 2013)
This work reconsiders debates about historical memory from the perspective of the theory of emotions. Its main claim is that the demise of the Spanish empire in 1898 spurred a number of contradictory emotional responses, ranging from mourning and melancholia to indignation, pride, and shame. It shows how intellectuals sought to reimagine a post-Empire Spain by drawing on myth and employing a predominantly emotional register.